SEJARAH PERKEMBANGAN HUKUM WARIS DI INDONESIA - Iim Fahimah (Universitas Islam Negeri Fatmawati Sukarno, 2018)
In this discussion the development of inheritance law was stated, from the time before colonialism until the time of independence. In the development of inheritance law before the colonial period, the empire and the sultanate applied inheritance law as a living law in the community as well as a culture of Indonesian law in its time. When the Dutch East Indies government arrived, Indonesia had implemented Islamic religious law, which then continued and recognized its legal authority, Van den Berg conceptualized Staatsblat 1882 Number 152 which contained provisions for indigenous people or colonized people, religious laws must be applied in his environment. Snouck Hoergronje, advisor to the Dutch East Indies Government, initiated the receptie theory of Islamic issues and domestic children who pro- posed “Islam can apply if it has been perceived by customary law”, so adat is what determines the existence or absence of Islamic law. Furthermore, at the time of independence Indonesian Islamic law experts tried to make Islamic law a national law, with the effort of national seminars in the formation of law, Islamic law was made as one of the sources in addition to European law and Customary law